2002
DOI: 10.1105/tpc.005793
|View full text |Cite
|
Sign up to set email alerts
|

The Tomato R Gene Products I-2 and Mi-1 Are Functional ATP Binding Proteins with ATPase Activity

Abstract: Most plant disease resistance (R) genes known today encode proteins with a central nucleotide binding site (NBS) and a C-terminal Leu-rich repeat (LRR) domain. The NBS contains three ATP/GTP binding motifs known as the kinase-1a or P-loop, kinase-2, and kinase-3a motifs. In this article, we show that the NBS of R proteins forms a functional nucleotide binding pocket. The N-terminal halves of two tomato R proteins, I-2 conferring resistance to Fusarium oxysporum and Mi-1 conferring resistance to root-knot nemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
323
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 373 publications
(338 citation statements)
references
References 38 publications
11
323
0
4
Order By: Relevance
“…Subsequent analysis revealed that it is a novel nucleotide binding protein related to zinc carboxypeptidases. In addition, the proteins encoded by disease-resistant genes in most plants contain ATP/GTP binding motifs, such as kinase-1a, kinase-2, and kinase-3a motifs, which confer resistance on the host tomato against Fusarium oxysporum , root-knot nematodes or potato aphids [39]. However, this study is the first to confirm the acid-resistance of the ATP/GTP binding protein.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequent analysis revealed that it is a novel nucleotide binding protein related to zinc carboxypeptidases. In addition, the proteins encoded by disease-resistant genes in most plants contain ATP/GTP binding motifs, such as kinase-1a, kinase-2, and kinase-3a motifs, which confer resistance on the host tomato against Fusarium oxysporum , root-knot nematodes or potato aphids [39]. However, this study is the first to confirm the acid-resistance of the ATP/GTP binding protein.…”
Section: Discussionmentioning
confidence: 94%
“…Given its central role in NB-LRR function, surprisingly little is known about the role of nucleotide binding in NB-LRR activation. In fact, nucleotide binding has been demonstrated unequivocally for only two plant NB-LRR proteins, I-2 and Mi-1, both from tomato (Tameling et al, 2002). The NB domains of these two proteins were expressed in Escherichia coli and shown in a filter-binding assay to specifically bind ATP rather than other nucleoside triphosphates.…”
Section: What Is the Role Of Nucleotide Binding In Nb-lrr Protein Funmentioning
confidence: 99%
“…The TIR subclass is found in dicot species whereas the non-TIR subclass with a coiled-coil (CC) structure occurs among both the monocot and dicot plants [11,10]. The CC domain with a coiled-coil structure is implicated in specific interactions with other proteins and also facilitates dimerization [12]. The CC-NB-LRR protein Rx of potato is found to interact with the Potato virus X (PVX) coat protein conferring resistance to PVX [13] and the Arabidopsis RPS4 gene is involved in resistance to Avr Rps4 of bacterial pathogens [14].…”
Section: Introductionmentioning
confidence: 99%